TRADE UNION AS A SOCIAL PARTNER IN IMPROVING PROFESSIONAL SUPPORT FOR TEACHERS - Grīnfelde, Anda; Paula, Līga; Vanaga, Inga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Social dialogue involving all social partners is very important in shaping sectoral policies, therefore an implementation of educational reforms and their evaluation should take place in close cooperation between policy makers, employers' and workers' organizations. In 2018, within the context of current educational reforms in Latvia, the Latvian Trade Union of Education and Science Employees conducted an on-line survey of the teachers aiming to identify problems in teachers’ professional support. The survey indicated a gap between political debate and the reality faced by teachers in the process of implementation of reforms. The respondents acknowledged the role of the trade union in improving the professional support for teachers and emphasized its role in social dialogue to strengthen it. Although most of the teachers are satisfied with a professional support during introduction of competence-based educational content, respondents do not feel sufficiently involved in the planning and designing reforms. They believe that the needs of educators for the qualitative implementation of reforms are not being identified. Therefore, the trade union should focus on the protection of labour rights as well as the development of a professional support system and content of education policy.